An Analysis of Medical Dispute Resolution in Cases Of Medical Personnel Negligence From an Administrative Law Perspective - Sagala Parluhutan; Erni Rianti Hardjoko; Lianawati Lianawati; Maulidina Kurniawati; Ahmad Jaeni; Arief Fahmi Lubis (Faculty of Law, Universitas Pekalongan, 2025)
Hospital service standards are closely linked to a hospital’s ability to provide healthcare services following its qualifications. This study aims to demonstrate how declining public trust in doctors has led to rising lawsuits, often associated with perceived failures in medical treatment. This qualitative research employs a descriptive approach to systematically and factually collect data promptly based on the conditions during the study. The findings indicate that doctors who commit medical negligence can be held legally accountable through both professional and non-professional institutions. Furthermore, non-professional dispute resolution can occur outside the court (non-litigation) or within the court system (litigation).